Provision of Water Services to Rural Population of Maldives Through Public Private Partnership (PPP) - Azim, Adam (2008)
The paper aims to identify the most appropriate method of Public Private Partnership (PPP) suitable for provision of water services to Maldives rural community and the extent to which rural community is prepared for a full cost recovery service provision system. The result of the study shows that there are many barriers for privatization of water services in Maldives rural islands. Therefore, it is vital to have a strategic plan which is phased out into stages. Such as, among others first to conduct awareness programs to make community aware that sustainable water services can only be provided by having a full cost recovery water provision, institution building and to introduce proper water regulatory system.